E-030 Antiplatelet therapy is associated with better outcomes in patients with moyamoya disease. a meta-analysis. (4th August 2020) - Suheel, M; Eagles, M; Almekhlafi, M
Abstract : Introduction: Moyamoya disease causes progressive stenosis of the supraclinoid internal carotid arteries with subsequent development of moyamoya collaterals. The mainstay treatment is surgical revascularization using direct or indirect bypass techniques. The use of antiplatelet agents is advocated to facilitate blood flow, maintain bypass patency, and reduce thrombotic events. We searched published literature to determine the benefits of antiplatelet therapy in this patient population. Methods: We performed a literature search of published papers in the English language using EMBASE, PUBMED, and Web of Science databases. With the assistance of a librarian, we used various combinations of keywords such as Moyamoya disease, ischemic stroke, hemorrhagic stroke, antiplatelet, and the names of individual antiplatelet agents. Titles and abstracts were screened by the first two authors (MAS and MEE), with a full-text review of relevant papers. Articles were included if they examined the effect of antiplatelet therapy on ischemic or hemorrhagic stroke or survival in patients with moyamoya disease. Results: Out of 132 retrieved studies, we identified five eligible studies published between 2014 and 2019 and included 26, 605 patients (9499 on antiplatelet therapy, and 17106 controls) with follow up ranging from post-operative period to 6.3 years. Only one study had a prospective design and two studies were multi-center. Three of the studies included post-bypass patients, and one included only asymptomatic moyamoya disease. The antiplatelet therapy regimens varied across the studies and included ASA, clopidogrel, or cilostazol.Three studies had a control arm that did not receive any antiplatelet therapy. In these studies, the pooled risk for a composite outcome (any ischemic or hemorrhagic stroke, or death) was lower in the antiplatelet group compared to controls (9% vs 11%; relative risk 0.85, 95% CI: 0.79 to 0.92). Conclusions: The use of antiplatelet therapy in patients with moyamoya disease may confer better stroke-free survival. Multicenter prospective studies with a uniform antiplatelet protocol are needed to elucidate the potential benefits of this intervention. Disclosures: M. Suheel: None. M. Eagles: None. M. Almekhlafi: None.